Raziskave nosilnega okvira vozila Šinkovec MM - Malnarič, Vili (Strojniški vestnik, 1999)
For all vehicles on the public highway it is necessary to obtain a motor vehicle approval document. For a unique prototype vehicle it is also required to have the necessary certificates for the strength and/or functional suitability of all the vital vehicle components. One of the most vital components of the Šinkovec MM vehicle is the vehicle's tube frame which offers high-strength support for the other elements of the vehicle. Strength calculations on the vehicle's tube frame have been made on the basis of extreme loads which were, in a computer suported strength calculation, applied on a FEM model of the vehicle's tube frame in the form of mass inertia forces occuring as a result of the action of the acceleration field on the masses of particular components of the vehicle. The strength calculation includes the verification of the stress state as a result of static and dynamic loads on the vehicle's tube frame.
Keywords: konstrukcije nosilne; dinamika vozil; izračuni trdnostni; metode končnih elementov; vozila; obremenitve; dinamika; trdnost